Room‐Temperature Stimulated Emission and Lasing in Recrystallized Cesium Lead Bromide Perovskite Thin Films. Issue 39 (12th August 2019) - Pourdavoud, Neda; Haeger, Tobias; Mayer, Andre; Cegielski, Piotr Jacek; Giesecke, Anna Lena; Heiderhoff, Ralf; Olthof, Selina; Zaefferer, Stefan; Shutsko, Ivan; Henkel, Andreas; Becker‐Koch, David; Stein, Markus; et al.
Abstract: Cesium lead halide perovskites are of interest for light‐emitting diodes and lasers. So far, thin‐films of CsPbX3 have typically afforded very low photoluminescence quantum yields (PL‐QY < 20%) and amplified spontaneous emission (ASE) only at cryogenic temperatures, as defect related nonradiative recombination dominated at room temperature (RT). There is a current belief that, for efficient light emission from lead halide perovskites at RT, the charge carriers/excitons need to be confined on the nanometer scale, like in CsPbX3 nanoparticles (NPs). Here, thin films of cesium lead bromide, which show a high PL‐QY of 68% and low‐threshold ASE at RT, are presented. As‐deposited layers are recrystallized by thermal imprint, which results in continuous films (100% coverage of the substrate), composed of large crystals with micrometer lateral extension. Using these layers, the first cesium lead bromide thin‐film distributed feedback and vertical cavity surface emitting lasers with ultralow threshold at RT that do not rely on the use of NPs are demonstrated. It is foreseen that these results will have a broader impact beyond perovskite lasers and will advise a revision of the paradigm that efficient light emission from CsPbX3 perovskites can only be achieved with NPs. Abstract : Highly efficient photoluminescence (PL‐QY = 68%), amplified spontaneous emission, and low‐threshold lasing in thin films of cesium lead bromide at room temperature are shown. Importantly, the films are not based on nanocrystals or quantum dots but consist of extended continuous layers that are formed upon recrystallization of as‐deposited layers by thermal imprint.